Purification and characteration of xylanase from Aspegillus oryzae VTCC F187 - Tuyen, Do Thi; Thu Huyen, Hoang; Sy Le Thanh, Nguyen; Thi Yen, Hoang; Thi Mai Anh, Dao (Vietnam Journal of Biotechnology, 2021)
Xylanase is produced by many bacteria and fungi, among which Aspergillus oryzae is considered as a potential source. In this study, a xylanase was isolated and purified from the crude culture filtrate of Aspergillus oryzae VTCC F187 after 7 days of growth on the optimal culture containing 7% corncob and 5% soybean powder under liquid-state fermentation. After two steps purification process including gel filtration chromatography (Sephadex G-75) incorporating with anion-exchange chromatography (DEAE-sephadex), obtained xylanase was purified with the yield and purity of 24.9% and 3.91 fold, respectively. The molecular mass of the purified xylanase determined by SDS–PAGEwas 32 kDa with a specific activity of 1268.0 U/mg towards 1% (w/v) of birch wood xylan. The xylanase displayed its optimum activity at 60°C, pH 6.5, and the enzyme remained active effectively within pH 3.0–5.0 and at the temperature below 37°C. Some substances were tested at concentration of 2% (v/v) such as β-mercaptoethanol, DMSO, Tween 80 and 10 mM NaN3 slightly decreased xylanase activity and reached over 85%. While EDTA 10 mM and SDS at concentration of 2% inhibited more strongly, xylanase activity was only 77.6% and 56.6% comparing with control one, respectively. The biochemical characteristics suggested that the xylanase has a potential application, including use as a feed enzyme or using hydrolysis to produce environmentally friendly Bio-products.